Resting-state functional magnetic resonance imaging-based identification of altered brain the fractional amplitude of low frequency fluctuation in adolescent major depressive disorder patients undergoing electroconvulsive therapy - Wang, Xing-Yu; Tan, Huan; Li, Xiao; Dai, Lin-Qi; Zhang, Zhi-Wei; Lv, Fa-Jin; Yu, Ren-Qiang (Frontiers in Psychiatry, 2022)
Purpose: While electroconvulsive therapy (ECT) has been repeatedly been shown to effectively and efficiently treat the major depressive disorder (MDD), the mechanistic basis for such therapeutic efficacy remains to be firmly established. As such, further research exploring the ECT-based treatment of MDD in an adolescent population is warranted. Methods: This study included 30 treatment-naïve first-episode MDD patients and 30 healthy control (HC) individuals (aged 12-17 years). All participants were scanned using rs-fMRI, and the 30 MDD patients were scanned again after two weeks of the ECT treatment period. Intrinsic local activity in each voxel was assessed based on the fALFF parameter, with all fALFF analyses being completed using the REST application. Correlations between ECT-related changes in fALFF and clinical parameters were additionally examined. Results: Relative to HCs, MDD patients exhibited increased fALFF values in the right inferior frontal gyrus (ORBinf), inferior occipital gyrus (IOG), and the left middle frontal gyrus (MFG) at baseline. Following ECT, these patients exhibited significant increases in fALFF values in the right medial superior frontal gyrus (SFGmed), dorsolateral superior frontal gyrus (SFGdor), anterior cingulate, and paracingulate gyrus (ACG), median cingulate and paracingulate gyrus (DCG), and left MFG. MDD patient HAMD scores were negatively correlated with fALFF values when analyzing pre-ECT vs. post-HCT ∆HAMD and fALFF values in the right SFGmed, SFGdor, and the left MFG. Conclusions: These data suggest that ECT induced altered fALFF in some regions of the brain, suggesting that these alterations may serve as a neurobiological indicator of ECT effectiveness in MDD adolescents.